Evaluation of Governmental Institutional Performance (After 2014) and Its Impact on Iraqi National Security: An applied study in the Ministry of the Interior / Ancy of the Ministry for Intelligence and Federal Investigations - alyasiry, akram; Mahmood Kareem, Aqeel (Iraqi Journal for Administrative Sciences, 2024)
The present research aims at recognizing،the governmental institutional performance evaluation and its impact on Iraqi national security. The study was applied at the Iraqi Ministry of Interior, specifically in Federal Intelligence &Investigations Agency (FIIA). The intentional sample method was used, that included several functional levels (general directors, directors of directorates, directors of departments and directors of sections. 124 questionnaires were distributed to all members of the targeted sample, and with the continuous follow-up of the researcher, all the questionnaire papers distributed to the sample members were retrieved, and when sorting the questionnaire papers, 15 of them appeared, among them, 15 abnormal or incomplete questionnaires, thus, the total number of the correct and used questionnaires is 109 in this study. In order to achieve the goal of the study, a hypothetical scheme was built that gives an initial perception of the shape of the studied relationships, and for the purpose of analyzing the data, the researcher used a set of advanced statistical tests by adopting structural models. The most important conclusion of the present study is that the institutional performance evaluation became a basic advantage and trait of institutions of different specializations. As a result of the comparisons that are relied upon through the actual required results, it plays a significant positive role in supporting the national security system.